Financing Management in Islam-Based Schools in the City of Tasikmalaya - Krisna Sujaya (Dinamika Ilmu, 2022)
The purpose of this study was to analyze budget planning to improve education in Islamic-based schools, organize and implement financial management in improving the quality of education, as well as the monitoring and accountability system for financing education in Islamic-based schools in Tasikmalaya City. The research design is qualitative combined with percentage descriptive. Data collection uses observation and interview methods, as well as documentation. The data analysis technique uses the Miles and Hubermann interactive analysis model which includes four stages, namely data collection, data reduction, data presentation according to the classification of themes, and drawing conclusions. The results of the study found that 1) education budget planning was prepared and stated in the form of a school income and expenditure budget plan which was prepared at the end of each year by establishing all program plans and the budget for each program, involving internal school stakeholders through meetings, 2) organizing funding Education starts from the source of the funds themselves, 3) budget execution is used according to plan with slight modifications in real implementation, 4) the supervision of education financing is carried out by foundations, and 5) the responsibility for school financing is left to school committees, foundations, and education offices.